2020
DOI: 10.1111/hsc.12939
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of healthcare utilisation for low back pain: A population‐based study in Ethiopia

Abstract: Low back pain (LBP) remains one of the major public health problems worldwide. However, in low‐income countries, such as those in Africa, the epidemiological data on healthcare utilisation for LBP are lacking due to more pressing problems such as infectious diseases, to which the majority of health resources are channelled. Therefore, this study aimed at investigating the determinants of healthcare utilisation for LBP in the general population of Ethiopia. A population‐based cross‐sectional study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…The new tool may promote assessment of beliefs about chronic pain and also inform interventions to improve health outcomes of Yoruba speaking patients with chronic LBP. Anecdotal and empirical reports indicate that African patients with chronic pain have psychosocial problems, in this case, unhelpful beliefs, that have strong cultural undercurrents which in turn affect their health seeking behaviour [39,40]. Early identification of patients with unhelpful beliefs about LBP is of utmost importance.…”
Section: Discussionmentioning
confidence: 99%
“…The new tool may promote assessment of beliefs about chronic pain and also inform interventions to improve health outcomes of Yoruba speaking patients with chronic LBP. Anecdotal and empirical reports indicate that African patients with chronic pain have psychosocial problems, in this case, unhelpful beliefs, that have strong cultural undercurrents which in turn affect their health seeking behaviour [39,40]. Early identification of patients with unhelpful beliefs about LBP is of utmost importance.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the remaining 543 individuals who reported at least 1 presentation to any of the health institutions for their LBP in the past 1‐year were included in the analysis of this paper (Figure 1). The detailed procedure that includes sample size calculation, sampling technique, the identification of individuals with LBP, and data collection, is described elsewhere 27 …”
Section: Methodsmentioning
confidence: 99%
“…The detailed procedure that includes sample size calculation, sampling technique, the identification of individuals with LBP, and data collection, is described elsewhere. 27…”
Section: Study Sample Sampling Procedure and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2020 population study in Central Ethiopia (N = 1812) found that 30% (95% CI 27.9-33.2) of the population had sought health care for low back pain in the previous year. 6 Of these 77% were treated with injected medications. There was a strong relationship between educational level and receiving back pain treatment, with those with a degree more likely to receive treatment compared to people with no education (adjusted proportion ratio = 1.68 [95% CI 1.44-1.99]).…”
Section: Many Patients With Low Back Pain Are Still Receiving the mentioning
confidence: 99%